English Speakers in the Laurentides Face Growing Economic Challenges, New Report Shows - Provincial Employment Roundtable (PERT) (2024)

Socio-Demographic Characteristics of Visible Minorities in MRC de Thérèse-De Blainville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Thérèse-De Blainville.

Socio-Demographic Characteristics of Visible Minorities in RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS des Laurentides.

RTS des Laurentides - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Employment Profile of English Speakers in the Laurentides - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Les Laurentides’ English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues for English-speaking workers in Les Laurentides, as well as preliminary recommendations to help improve their labour market outcomes.

[Newsletter] - 4 Korners Family Resource Center (2023)

[Newsletter] - 4 Korners Family Resource Center (2023)

[Newsletter] - 4 Korners Family Resource Center (2023)

4Korners Activities - 4 Korners Family Resource Center (2023)

4Korners Activities - 4 Korners Family Resource Center (2023)

4Korners Activities - 4 Korners Family Resource Center (2023)

4Korners Activities : Hello March! - 4 Korners Family Resource Center (2023)

4Korners Activities : Hello February! - 4 Korners Family Resource Center (2023)

4Korners Activities - 4 Korners Family Resource Center (2023)

Impact Report 2022-2023 - 4Korners (2023)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and Mirabel - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Antoine-Labelle - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Argenteuil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Deux-Montagnes - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities Region of Laurentides and MRC Les Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS des Laurentides - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

Improving the Health and Well-being of English-speaking Seniors in the Laurentians, Québec : A Needs Assessment - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
This needs assessment was commissioned by the 4Korners Laurentian Community Network, a registered Canadian charitable organization founded in 2005, which connects individuals of the Laurentians with programs and services to meet their needs in a secure and inclusive environment. The objective was to identify the needs of the aging English-speaking population in the Laurentians and to determine if they are currently being met. The First Nations Adult Education School Council conducted the assessment in partnership with S.O.A.R. Solutions, a consulting firm. The work was overseen by a committee (the Seniors’ Needs Assessment Committee, SNAC), made up of 4Korners employees, volunteers, the Elders’ Community Worker from the Kanesatake Health Center and project consultants from the First Nations Adult Education School Council.

Impact Report 2021-2022 - 4Korners (2022)

Employment Profile of English Speakers in Laurentides - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by English-speaking communities in the Laurentides by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys the economic structure of the Laurentides, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

4Korners Activities - 4 Korners Family Resource Center (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)

4Korners Activities - 4 Korners Family Resource Center (2021)

Impact Report 2020-2021 - 4Korners (2021)

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

RTS des Laurentides - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

4Korners Activities - 4 Korners Family Resource Center (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)

4Korners Activities ONLINE - 4 Korners Family Resource Center (2020)

4Korners Activities ONLINE - 4 Korners Family Resource Center (2020)

4Korners April 2020 - 4 Korners Family Resource Center (2020)

Impact Report 2019-2020 - 4Korners (2020)

Profile of Laurentian English-speaking Youth 15-29 - 4Korners (2020)
According to data published by the Institut de la statistique du Québec in 2020, the population living in the administrative regions of the province has significantly changed between 2019 and 2021, being directly affected by the social impacts caused by the COVID-19 pandemic and its implications for out-migration, mobility, workforce attractivity, work/life balance, lifestyle habits and leisure activities. As a result, it is estimated that 632,000 inhabitants were living in the Laurentian region as of July 1, 2020. This represents an increase of 17.7% for the year 2019-2020, which is higher than the average rate across the province (8.5%) for that year. In fact, it is important to highlight that this region presents the largest increase since the outbreak of the pandemic in March 2020.

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

Making a Difference in the Laurentians - LESAN (2020)

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

August 2019 4K Newsletter - 4 Korners Family Resource Center (2019)

June 2019 4K Newsletter - 4 Korners Family Resource Center (2019)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2019)

May 2019 4K Newsletter - 4 Korners Family Resource Center (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)

Impact Report 2018-19 : English Community Services & Support - 4Korners (2019)

Community Health Education Program (CHEP) 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)
The CHSSN Community Health Education Program (CHEP) serves the urban, rural and remote English-speaking communities around the province of Quebec, providing health and social information and support via video conferencing through the RUIS (McGill) Telehealth system. Twenty community NPI networks funded under the CHSSN Network Partner Initiative (NPI) from across the province of Quebec participated, by attending the CHEP video conferences and by hosting a CHEP DVD viewing session. The following report highlights the Community Health Education Program (CHEP) activities for the period from April 1, 2018, to March 31, 2019.

Vitality - Community Health and Social Services Network (CHSSN) (2019)
Keywords: Official Language Minority Community (OLMC)

Who We Are - Community Health and Social Services Network (CHSSN) (2019)

David Graham - Liberal Candidate for Laurentides-Labelle - Graham, David (2019)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2019)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2019)

Annual Report 2018-2019 - Leading English Education and Resource Network (LEARN) (2019)

Laurentian English Services Advisory Network - LESAN (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Antoine-Labelle - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Argenteuil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Deux-Montagnes - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC La Rivière-du-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Les Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Les Pays-d'en-Haut - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Mirabel - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Thérèse-de Blainville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2018)

Impact Report 2017-18 : English Community Services & Support - 4Korners (2018)

Adaptation Initiative Project Guide 2014-2018 - Community Health and Social Services Network (CHSSN) (2018)
The CHSSN’s initiative to adapt health and social services is supported by an investment from Health Canada, through the Roadmap for Canada's Official Languages 2013–2018: Education, Immigration, Communities. This initiative is being undertaken in partnership with the Ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded in order to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English. The agreement also divided the roles and responsibilities among the CHSSN, the MSSS, and the health and social services agencies.

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2018)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2018)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2018)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2018)

Annual Report 2017-2018 : Leading the Way - Leading English Education and Resource Network (LEARN) (2018)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)

General By-Laws of The 4 Korners Family Resource Centre - 4Korners (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2017)

LAURENTIANS NEWSLETTER - 4 Korners Family Resource Center (2017)

[Newsletter] - 4 Korners Family Resource Center (2017)

Annual Report : 2016-2017 - 4Korners (2017)

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

David Graham - Graham, David (2017)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2017)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2017)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2017)

Annual Report 2016-2017 - Leading English Education and Resource Network (LEARN) (2017)

Demographic Profiles of English-speaking Communities : RTS des Laurentides (1510) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS d'Antoine-Labelle (1511) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS d'Argenteuil (1514) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de Deux-Montagnes - Mirabel-Sud (1515) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de La Rivière-du-Nord - Mirabel-Nord (1516) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de Thérèse-de Blainville (1517) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS des Laurentides (1512) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS des Pays-d'en-Haut (1513) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

CLC Chronicles 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)

[Newsletter] - 4 Korners Family Resource Center (2016)

[Newsletter] - 4 Korners Family Resource Center (2016)

[Newsletter] - 4 Korners Family Resource Center (2016)

[Newsletter] - 4 Korners Family Resource Center (2016)

Update - Leading English Education and Resource Network (LEARN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

[Newsletter] - 4 Korners Family Resource Center (2016)

[Newsletter] - 4 Korners Family Resource Center (2016)

[Newsletter] - 4 Korners Family Resource Center (2016)

[Newsletter] - 4 Korners Family Resource Center (2016)

[Newsletter] - 4 Korners Family Resource Center (2016)

Annual Report : 2015-2016 - 4Korners (2016)

English Language Services Directory: Laurentians Region : 2016 - 4Korners (2016)

Children 0 to 5 and their Parents : RTS des Laurentides - Community Health and Social Services Network (CHSSN) (2016)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2016)

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2016)

Provincial Resource Team Report 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)
Over the last ten years, English schools in Quebec have increasingly embraced the dual role of supporting student perseverance and contributing to the vitality of their English-speaking communities. With more than 80 schools and adult education centres across the province now part of the Community Learning Centre (CLC) network, it is evident that School Boards are adopting a new way of thinking about school and community partnerships. This “integrated focus on academics, services, supports and opportunities leads to improved student learning, stronger families and healthier communities. Schools become centers of the community”
Keywords: Official Language Minority Community (OLMC)

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Regional Mini Portraits - Pocock, Joanne (2016)
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

[Newsletter] - 4 Korners Family Resource Center (2015)

[Newsletter] - 4 Korners Family Resource Center (2015)

[Newsletter] - 4 Korners Family Resource Center (2015)

Annual Report : 2014-2015 - 4Korners (2015)

CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)
Keywords: Official Language Minority Community (OLMC)

2013-2014 Annual Report of CLC Activities - Leading English Education and Resource Network (LEARN) (2014)
Keywords: Official Language Minority Community (OLMC)

June 12, 2014 - Leading English Education and Resource Network (LEARN) (2014)

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Laurentien (0603) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS d'Antoine Labelle (1504) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Saint Jerome (1502) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de St Therese de Blainville (1503) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS des d'Argenteuil (1507) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS des Pays d'en Haut (1505) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS des Sommets (1506) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Lac des Deux Montagnes (1501) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Annual Report : 2013-2014 - 4Korners (2014)

Community Learning Centres : Changing Lives and Communities Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2013)
This year the 37 Community Learning Centres across Quebec worked collaboratively with more than 700 local, regional, provincial, and national partners, to leverage in excess of $3 million of in-kind services and resources to serve their schools and communities. CLCs are doing more than just leveraging resources; they are changing lives and communities. They serve as a place for education and community development, and have become an important part of collaborative community change efforts. The stories and best practices highlighted in this annual report capture the essence of the initiatives being implemented by CLCs to achieve change and progress in English speaking communities across Quebec. Highlights of the activities undertaken in 2012-2013 begin with how one of our most important stakeholder groups, our teachers, are engaging with our initiative. The Community-Based Learning approach is just one example of the many strategies CLCs are adopting to impact students and develop a culture of lifelong learning. This year’s activities also included many examples of in-school and after-school activities in which CLC students are learning about incorporating healthy living options into their lives as well learning about aboriginal culture and building relationships between aboriginal and non-aboriginal communities. CLCs mobilize community and partner support to address current and important needs in our schools, including improving school climate and reducing bullying. Their activities for adults and seniors demonstrate to students that learning truly is a lifelong process. Engaging parents before their children have even entered school and continuing to find ways to connect and support parents throughout school life is an ongoing and important part of our work.

June 13, 2013 - Leading English Education and Resource Network (LEARN) (2013)

Annual Report : 2012-2013 - 4Korners (2013)

Update - Leading English Education and Resource Network (LEARN) (2012)

Annual Report : 2011-2012 - 4Korners (2012)

Annual Report : 2010-2011 - 4Korners (2011)

Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)

Annual Report : 2009-2010 - 4Korners (2010)

2009-10 Annual Report - Leading English Education and Resource Network (LEARN) (2010)
In a province as vast as Quebec, and with schools and school boards scattered over an enormous geographic expanse, the notion of bringing people together to create a COMMUNITY of collaboration may appear daunting, if not impossible. In reality, when people share similar interests and common goals, those physical impediments can quickly disappear. This is especially true when the ultimate objective is the academic success of our children in elementary and high schools. LEARN’s focus is to serve as a catalyst and facilitator for the creation of communities of collaboration composed of educators, parents and students across the province. It is our organization’s objective to make every effort possible to get the well-intentioned forces within the English educational milieu together to share the wealth of knowledge and experience that resides there.

Naming the Laurentians : A History of Place Names 'Up North' - Graham, Joseph (Les Editions Main Street Inc., 2005)

Programme de responsabilité sociale de l’entreprise / Corporate Social Responsibility Program - 4Korners

David Graham - MP for Laurentides-Labelle - Graham, David

Together We Can Help Create an Ideal Learning Environment for All - Leading English Education and Resource Network (LEARN)